2015
DOI: 10.1016/j.forsciint.2015.02.020
|View full text |Cite
|
Sign up to set email alerts
|

The importance of microbiological testing for establishing cause of death in 42 forensic autopsies

Abstract: Microorganisms have always been one of the great challenges of humankind, being responsible for both high morbidity and mortality throughout history. In a forensic setting microbiological information will always be difficult to interpret due to lack of antemortem information and changes in flora postmortem. With this study we aim to review the use of microbiological procedures at our forensic institute. In a retrospective study including 42 autopsies performed at our Institute, where microbiological test had b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 24 publications
1
12
0
2
Order By: Relevance
“…The interpretation of culture results from autopsy specimens is not straightforward and may be complicated further when the procedure is conducted many days after death, potentially providing greater opportunity for tissue autolysis and translocation of organisms to compartments they did not occupy in life [4042]. However, there is evidence to show that the time from death to autopsy does not have a major effect on false-positive bacterial results if the body is kept refrigerated [43,44]. One study, conducted among 507 infants with sudden and unexpected deaths, even suggests that a longer interval may allow for fewer false-positive results [45]; and there are reports of pathogens recovered from bodies in states of advanced decomposition [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…The interpretation of culture results from autopsy specimens is not straightforward and may be complicated further when the procedure is conducted many days after death, potentially providing greater opportunity for tissue autolysis and translocation of organisms to compartments they did not occupy in life [4042]. However, there is evidence to show that the time from death to autopsy does not have a major effect on false-positive bacterial results if the body is kept refrigerated [43,44]. One study, conducted among 507 infants with sudden and unexpected deaths, even suggests that a longer interval may allow for fewer false-positive results [45]; and there are reports of pathogens recovered from bodies in states of advanced decomposition [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of cause of death (i.e., the disease or injury that produces physiological disruption in the body leading to death), researchers such as Christoffersen (2015) have investigated the importance of microbiological testing. Studying autopsy results ( n = 42), the author reported that the cause of death could be determined in 42% of the cases via microbiological analysis.…”
Section: Major Themes In the Forensic Microbiology Literaturementioning
confidence: 99%
“…We describe specific protocols for different clinical scenarios, including wide sampling of fluids, tissues and swabs, as most protocols generally advocate [12,21].…”
Section: Protocols For Pmm Sampling In Different Clinical Scenariosmentioning
confidence: 99%
“…Although selection of specimens in PMM should be driven by the clinical context (symptoms, presentation, presumptive diagnosis), ante-mortem information is not always available in sudden death cases, and when available sometimes does not suggest an infectious COD. On such occasions samples should be collected if macroscopic findings suggest an infection [21].…”
Section: Protocols For Pmm Sampling In Different Clinical Scenariosmentioning
confidence: 99%